An Analysis of Cash Liquidation in Housing Redevelopment Process - With a Focus on Incheon Metropolitan City Redevelopment Projects - Nam, Ki Cheul; Lee, Young Han (KIEAE Journal, 2021)
Purpose: Cash settlements in redevelopment projects did not emerge as a big problem during the invigoration period of the housing market when profit margins could be earned through pre-sale. However, changes in development conditions are causing constant conflicts. Therefore, this study analyzed current matters concerning cash settlements with the cash liquidators as subjects. A field survey was conducted on various interests and requests calling out for improvement to criticize the cash settlement issue and formulate methods to resolve it. Method: Field surveys were carried out among cash liquidators and frequency analysis was conducted on the survey data. The study consisted of four steps: literature review, case study, field survey, and analysis and results. Results: Drawing from the comprehensive content cited above, this study investigated cash settlement issues involved in redevelopment projects with the cash settlers as subjects and analyzed various interests and requests for improvement. In conclusion, compensation for land and for properties that are obstructions along with a transparent redevelopment process should be scrutinized. In addition, incorporation of an evaluation method centered around cash settlers and revision of the compensation structure is considered necessary to increase compatibility with reality. KCI Citation Count: 0